Increasing legal and gender capacity for Nasyiatul 'Aisyiyah regional leaders of Klaten Regency - Indah Nur Shanty Saleh; Muhammad Habibi Miftakhul Marwa (Community Empowerment, 2022)
The purpose of this community service is to increase legal and gender capacity for Nasyiatul 'Aisyiyah regional leaders of Klaten Regency. Nasyiatul 'Aisyiyah cadres as young Muhammadiyah women are expected to be able to carry out the function of preaching amar ma'ruf nahi munkar in the midst of rampant practices of inequality and injustice against women and children. The method of implementing the school of law and gender for Nasyiatul 'Aisyiyah Regional Leaders, Klaten Regency through lectures, forum group discussion, and making campaign media which are uploaded on social media. Law and gender school activities provide increased understanding and skills for Nasyiatul 'Aisyiyah leaders and cadres with 72.7% agreeing and 27.3% strongly agreeing. However, participants increasingly have the courage to take a role and have a positive influence on the struggle for gender equality and justice in Klaten Regency in particular, and Indonesian women in general.